Pengungkapan Sustainability Report Pada Perusahaan Sub Sektor Jasa Penyedia Kesehatan Dan Sub Sektor Farmasi - Lembah Dewi Andini; Bimo Agusty; Keri Boru Hotang (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2024)
Purpose – This research aims to empirically test the influence ofprofitability and company size on the disclosure of Sustainability Reportsin companies in the health sector, the health services provider sub-sectorand the pharmaceutical sub-sector listed on theIndonesian stock exchangein 2018 - 2022.Design/methodology/approach – The population of this research is 30health sector companies listed on the Indonesia Stock Exchange. Thesample selection method in this research is based on sampling withpredetermined criteria. In this case, the sample studied was 11 companies.The Analysis technique used to test the hypothesis is multiple regressionanalysis using Eviews 9 software.Findings – The results of this research show that profitability has anegative and statistically insignificant effect on Sustainability Reportdisclosure, but for Company Size it has a positive and statisticallyinsignificant effect on Sustainability Report disclosure.Originality/value - This research discusses the influence of profitabilityand company size on Sustainability Reporting in health sector companies.